2021
DOI: 10.1128/jcm.00464-21
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Accurate Detection of Aminoglycoside-Modifying Enzymes and 16S rRNA Methyltransferases by Targeted Liquid Chromatography-Tandem Mass Spectrometry

Abstract: New and rapid diagnostic methods are needed for the detection of antimicrobial resistance to aid in the curbing of drug-resistant infections. Targeted liquid chromatography-tandem mass spectrometry (LC-MS/MS) is a method that could serve this purpose, as it can detect specific peptides of antimicrobial resistance mechanisms with high accuracy. In the current study, we developed an accurate and rapid targeted LC-MS/MS assay based on parallel reaction monitoring for detection of the most prevalent aminoglycoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…When peptides for other resistance mechanisms, such as ESBLs, carbapenemases ( Foudraine et al, 2019 ), fluoroquinolone resistance mechanisms ( Hassing et al, 2016 ), and aminoglycoside resistance mechanisms ( Foudraine et al, 2021a ) would be added to the current panel of CMY, E. coli cAmpC, OmpC and OmpF, a single multiplex LC-MS/MS assay would be able to detect several prevalent mechanisms that confer resistance to beta-lactams, fluoroquinolones and aminoglycosides in for instance E. coli . While such an assay could be used to confirm or rule out the presence of specific resistance mechanisms after routine susceptibility testing, it may be more beneficial to use it as a rapid screening test for important liquid cultures such as blood cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When peptides for other resistance mechanisms, such as ESBLs, carbapenemases ( Foudraine et al, 2019 ), fluoroquinolone resistance mechanisms ( Hassing et al, 2016 ), and aminoglycoside resistance mechanisms ( Foudraine et al, 2021a ) would be added to the current panel of CMY, E. coli cAmpC, OmpC and OmpF, a single multiplex LC-MS/MS assay would be able to detect several prevalent mechanisms that confer resistance to beta-lactams, fluoroquinolones and aminoglycosides in for instance E. coli . While such an assay could be used to confirm or rule out the presence of specific resistance mechanisms after routine susceptibility testing, it may be more beneficial to use it as a rapid screening test for important liquid cultures such as blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptic peptides from 6 to 20 amino acids without a cysteine and preferably without a methionine or a double lysine/arginine motif at the N- or C-terminus (ragged end) were selected as candidate peptides ( Supplementary Table 1 ). In addition to porin and β-lactamase peptides, internal quality control peptides were included from a previous study for verification of adequate sample pre-treatment ( Foudraine et al, 2021a ). General peptide uniqueness of all candidate peptides was assessed by performing BLASTp searches in the NCBI non-redundant protein sequence database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we demonstrated the possibility to detect different carbapenemase enzymes and aminoglycoside resistance mechanisms with high accuracy using LC-MS/MS (Foudraine et al, 2019(Foudraine et al, , 2021a. In these studies, resistance mechanisms were identified by detection of selected specific peptides, and SIL peptides were used to automate the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…+As previously reported (Foudraine et al, 2019).# As reported (Foudraine et al, 2022). * As previously reported (Foudraine et al, 2021a). "Anonymous" variants were unique β-lactamase variants similar to the reference sequence which were not (yet) annotated at the time of peptide selection.…”
Section: Assay Development: Concentration Of Stable Isotope Labeled P...mentioning
confidence: 88%